Different models of chemotherapy taking into account drug resistance stemming from gene amplification - Śmieja, Jarosław; Świerniak, Andrzej (1950- ) (Zielona Góra: Uniwersytet Zielonogórski)
This paper presents an analysis of some class of bilinear systems that can be applied to biomedical modelling. It combines models that have been studied separately so far, taking into account both the phenomenon of gene amplification and multidrug chemotherapy in their different aspects.
Keywords: biomedical modelling; infinite dimensional systems; multivariable control